USING LANGUAGE CAPABILITIES IN POETIC SPEECH (Proceedings of International Educators Conference, 2024)
In real poetry, neither a word nor a unit of language can be used for entertainment or to complete a text. Even simple speech sounds, syllables, words, phrases, expressions, adverbs and sentences can be used according to their meaning and meaning. Only then will each phonetic, morphological, lexico-semantic, syntactic unit of language become in its place a means of poetic interpretation; attracts; connects the student's psyche with the world of poetry. The poetry of Halima Khudoyberdiyeva is a literary phenomenon, which is a unique practical manifestation of these high requirements in our national literature, showing more and more aspects of linguistic and poetic research.